2018
DOI: 10.1007/s11557-018-1381-x
|View full text |Cite
|
Sign up to set email alerts
|

New phylogenetic insights into Saprolegniales (Oomycota, Straminipila) based upon studies of specimens isolated from Brazil and Argentina

Abstract: Saprolegniales is a complex and monophyletic order of oomycetes. Their members inhabit terrestrial, freshwater, and marine ecosystems and have a worldwide distribution. In these ecosystems, they are found as saprobes, parasites, or even pathogens of animals and plants of economic importance. In this study, a concatenate phylogeny of the partial LSU and complete ITS rDNA regions is presented, including isolates from Brazil and Argentina, which were sequenced after a detailed morphological analysis. Among the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…2007, Hulvey et al . 2007, Steciow et al 2013, Sandoval-Sierra et al 2014, Steciow et al 2014, Rocha et al 2018), the Rhipidiales has received relatively little attention, probably owing to a lower degree of cultivation success from environmental samples due to their often microaerophilic to anaerobic nature. Thus, it seems promising to undertake targeted sampling in oxygen-depleted limnic environments in order to gain further insights into these understudied organisms which might play an important role in nutrient cycling.…”
Section: Discussionmentioning
confidence: 99%
“…2007, Hulvey et al . 2007, Steciow et al 2013, Sandoval-Sierra et al 2014, Steciow et al 2014, Rocha et al 2018), the Rhipidiales has received relatively little attention, probably owing to a lower degree of cultivation success from environmental samples due to their often microaerophilic to anaerobic nature. Thus, it seems promising to undertake targeted sampling in oxygen-depleted limnic environments in order to gain further insights into these understudied organisms which might play an important role in nutrient cycling.…”
Section: Discussionmentioning
confidence: 99%
“…Saprolegniales are mainly predominantly freshwater saprophytes of plant and animal debris (Beakes and Sekimoto 2009). This order contains three families: Achlyaceae (four genera), Saprolegniaceae (11 genera) and Verrucalvaceae (7 genera) Molloy et al 2014;Beakes and Thines 2017;Rocha et al 2018). Amongst these, Achlya, Brevilegnia, Dictyuchus, Leptolegnia, Plectospira, Saprolegnia and Thraustotheca have been commonly reported to inhabit freshwater ecosystems (Czeczuga et al 2005;Mousavi et al 2009;Marano et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Before the replacement to this family, the genus Achlya was classified under the family Saprolegniaceae [5,6]. In members of this genus, primary aplanospores are discharged from sporangium, and before swimming away, stay near the exit of the sporangium until a ball of spores is formed [4,7]. Molecular phylogenetic studies have shown that Achlya s. lat.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, Rocha et al. [7] have transferred Achlya androgyna to Newbya . To date, approximately 80 species have been accepted in the genus Achlya (www.indexfungorum.org; [7]).…”
Section: Introductionmentioning
confidence: 99%